Morality and spirituality: The missing link for economic development in the 21st century - Kame, Greg (HTS teologiese studies, 2015)
Whilst religion may have been of relevance in the quest for material prosperity and economic advancement in the 16th century, it seems not to have such importance today. The declining rate of organised religion and the growth of secularism around the world progressively lead many to believe that if there is any truth particularly relevant for this century, it is no longer found in religion. In this paper, we argue that global leadership deficiencies and corruption (glaring as they may be) are not the root causes for the economic development challenges currently faced in Southern Africa and the rest of the world. They are simply the result of the root cause, which we maintain is a decline in moral and spiritual values in society, and unless national governments make some meaningful progress in these realms, this generation is headed for serious economic trouble.